2012
DOI: 10.1002/jbm.a.34455
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and biocompatibility of composite biomaterials fabricated from titanium and tricalcium phosphate by spark plasma sintering

Abstract: Important issues in developing hydroxyapatite (HAp)- and titanium (Ti)-based composite biomaterials for orthopedic or dental devices include the dissociation of HAp during fabrication and its influences in the microstructure and biocompatibility of the final composite. During the densification by sintering of HAp/Ti composites, Ti reacts with -OH freed from HAp to form TiO2 thus dissociated HAp into Ca3(PO4)2, CaO, CaTiO3, TiP, and so forth. To inhibit this reaction, composites were fabricated with Ti and 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
(108 reference statements)
0
13
0
1
Order By: Relevance
“…Although PECS suppresses the oxidation of Ti at 900°C, the formation of Ti 2 O was found in samples sintered at 1000°C. Mondal et al used the SPS technique to sinter β‐TCP and Ti powders at 1200°C temperature under 50 MPa pressure. Despite the retention of β‐TCP and Ti, this results in the formation of CaTiO 3 .…”
Section: Processing Of Ha‐ti Compositesmentioning
confidence: 99%
“…Although PECS suppresses the oxidation of Ti at 900°C, the formation of Ti 2 O was found in samples sintered at 1000°C. Mondal et al used the SPS technique to sinter β‐TCP and Ti powders at 1200°C temperature under 50 MPa pressure. Despite the retention of β‐TCP and Ti, this results in the formation of CaTiO 3 .…”
Section: Processing Of Ha‐ti Compositesmentioning
confidence: 99%
“…Hydroxyapatite (HA) and beta tricalcium phosphate (βTCP) are the most extensively studied calcium phosphates, and therefore, they are widely used in various applications, such as in biomaterials, ion exchangers, adsorbents, and catalysts . HA is also considered suitable for bone repairing, particularly in orthopedic implants to accelerate growth of surrounding bone because of the structural and chemical similarities between HA crystal and bone calcium phosphates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bioactive ceramic materials can be used for Ti implant surface modification to stimulate migration and adhesion of cells and proteins, as well as to accelerate bone growth. Several methods have been used to coat Ti‐based implant surfaces with HA or TCP although the major concern is the prevalence of fractures at the Ti/ceramic interfaces by chipping on friction during implant placement into bone.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained due to the thermal stability of the tricalcium phosphate ( Figure 1) and the less reactivity of iron in comparison with other metals like the titanium [15]. In fact, it has been reported that the spark plasma sintering of tricalcium phosphate-titanium powders has led to the partial degradation of the phosphate and the formation of CaTiO 3 phases [16]. For the TCP-Fe composite, no formation of CaO has been found as it is typical in the case of the hydroxyapatite-titanium composites.…”
Section: Discussionmentioning
confidence: 99%